Chlorogenic Acid Inhibits Proliferation, Migration and Invasion of Pancreatic Cancer Cells via AKT/GSK-3β/β-catenin Signaling Pathway - Chen, Xiaoliang; Liu, Binyu; Tong, Jiale; Bo, Jianing; Feng, Miao; Yin, Lili; Lin, Xiukun (Recent Patents on Anti-Cancer Drug Discovery, 2024)
Background: Chlorogenic acid (CA, United States Patent No. 10772340), a natural biologically active food ingredient, displays potent antitumor activity against a variety of cancer cells. However, the mechanism underlying its anticancer effect is not well elucidated.Objective: In the present study, we hope to dissect the mechanism underlying the anticancer effects of CA in pancreatic cancer cells.Methods: The cytotoxicity of CA in pancreatic cancer cells was determined by MTT assay. Flow cytometry was performed to evaluate the cells apoptosis, while a clonogenic assay was carried out to check the colony formation of cancer cells. Transwell assay was performed to assess the cells migration and invasion. The protein expression of AKT/GSK-3β/β-catenin signaling pathway was detected by Western Blot.Results: Our data indicated that CA inhibited the proliferation of PANC-28 and PANC-1 cells in a dose and time-dependent manner. CA was able to inhibit colony formation, migration, and invasion ability and trigger apoptosis in PANC-28 and PANC-1 cells. Further study showed that CA down-regulated the expression of AKT, p-AKT(Thr308), p-GSK-3β(Ser9), β-catenin, N-cadherin, and vimentin while enhancing the expression of cleaved-caspase 3 and cleaved-caspase 7 in PANC-28 and PANC-1 cells.Conclusion: Our study provides significant evidence that CA is able to inhibit the growth of pancreatic cancer via the AKT/GSK-3β/β-catenin signaling pathway.
Keywords: AKT/GSK-3β/β-catenin